2021
DOI: 10.1101/2021.08.03.454992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulating D1 rather than D2 receptor-expressing spiny-projection neurons corresponds to optimal antipsychotic effect

Abstract: Overactive dopamine transmission in psychosis is predicted to unbalance striatal output via D1- and D2-dopamine receptor-expressing spiny-projection neurons (SPNs). Antipsychotic drugs are thought to re-balance this output by blocking D2-receptor signaling. Here we imaged D1- and D2-SPN Ca2+ dynamics in mice to determine the neural signatures of antipsychotic effect. Initially we compared effective (clozapine and haloperidol) antipsychotics to a candidate drug that failed in clinical trials (MP-10). Clozapine … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…While the D1 agonist SKF38393 may have enhanced the negatively valenced sensory property of medial accumbens shell dopamine by elevating the activity of neurons expressing D1 receptors, it is equally likely that the relevant feature of this manipulation was broader reshaping of accumbal physiology. Consistently, recent work [80][81][82][83] describes unintuitive responses of striatal neurons to modulation of dopamine neurotransmission. The relationship between input stimulation, the profile of ventral striatal activity that follows, and motivated behaviour is complex, poorly described, and a major hurtle to treating psychopathologies characterized by striatal dysfunction.…”
Section: Discussionsupporting
confidence: 60%
“…While the D1 agonist SKF38393 may have enhanced the negatively valenced sensory property of medial accumbens shell dopamine by elevating the activity of neurons expressing D1 receptors, it is equally likely that the relevant feature of this manipulation was broader reshaping of accumbal physiology. Consistently, recent work [80][81][82][83] describes unintuitive responses of striatal neurons to modulation of dopamine neurotransmission. The relationship between input stimulation, the profile of ventral striatal activity that follows, and motivated behaviour is complex, poorly described, and a major hurtle to treating psychopathologies characterized by striatal dysfunction.…”
Section: Discussionsupporting
confidence: 60%
“…Because antipsychotics do not principally target them, striatal D1Rs could contribute to the treatment-resistant symptoms. Consistent with this idea, we recently found that clozapine, a highly efficacious antipsychotic drug with some pro-cognitive effects, preferentially normalized activity in D1R-expressing spiny projection neurons (SPNs) in the DMS under hyperdopaminergic conditions (50,51). By contrast, haloperidol affected both D1-and D2-SPN activity following amphetamine treatment (50).…”
Section: Discussionmentioning
confidence: 81%
“…Consistent with this idea, we recently found that clozapine, a highly efficacious antipsychotic drug with some pro-cognitive effects, preferentially normalized activity in D1R-expressing spiny projection neurons (SPNs) in the DMS under hyperdopaminergic conditions (50,51). By contrast, haloperidol affected both D1-and D2-SPN activity following amphetamine treatment (50). These data potentially explain why haloperidol partially rescued working memory in capsaicin-treated TRPV1 mice, and suggests that drugs that preferentially normalize D1-SPN activity may have greater therapeutic advantages over drugs like haloperidol that principally block D2Rs (50).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…With respect to non-glutamatergic approaches, despite many similarities with the phenotype of dopamine D 2 receptor antagonists in preclinical studies, multiple PDE10 inhibitors failed due to lack of efficacy in clinical development. Recent speculation attributes failures of such inhibitors to their only modulating indirect spiny projection neurons in the striatum and / or the additional effects on cyclic GMP with respect to modulation of cyclic AMP by dopamine D 2 receptor antagonists [31].…”
Section: The Past and The Present Of Schizophrenia Drug Developmentmentioning
confidence: 99%